Evaluation of F1 Hybrids of Pumpkin (Cucurbita moschata Duch. Ex Poir) for Yield and Quality - Tamil Selvi, N A; Jansirani, P; Pugalendhi, L (Journal of Horticultural Sciences, 2013)
An investigation was carried out to study the performance of 36 hybrids of pumpkin (Cucurbita moschata Duch. ex Poir) through Line x Tester mating design. Observations were recorded on the traits, viz., vine length, days to first female flower appearance, node number for first female flower appearance, sex ratio, days to first harvest, fruit number per vine, fruit weight, flesh thickness and fruit yield per vine, besides quality traits such as total carbohydrate content, total carotenoid content and crude fibre content in the fruit. Among the 36 hybrids of pumpkin studied, the cross 'Kasi Harit x Avinashi Local' excelled in yield per vine, followed by the crosses 'Vadhalagundu Local x CO-2' and 'Narendra Uphar x CO-2', respectively. Thus, first generation hybrids can be well-utilized for exploiting hybrid vigour to achieve improved quality.
Keywords: Hybrids; Pumpkin; Evaluation; Line x Tester